Association Between Patient Race and Ethnicity and Outcomes With COVID-19: A Retrospective Analysis From a Large Mid-Atlantic Health System. (May 2023) - Rao, Anirudh; Alnababteh, Muhtadi H.; Avila-Quintero, Victor J.; Flores, Jose M.; Laing, Nina E.; Boyd, David A.; Yu, Jennifer; Ahmed, Naheed; Groninger, Hunter; Zaaqoq, Akram M.
Background: Members of racial and ethnic minority groups have been disproportionately impacted by coronavirus-2019 (COVID-19). The objective of the study is to describe associations between race and ethnicity on clinical outcomes such as need for mechanical ventilation and mortality. Methods: Retrospective cohort study of patients with severe COVID-19 infection admitted within a large, not-for-profit healthcare system in the mid-Atlantic region between March and July, 2020. Patient demographic data and clinical outcomes were abstracted from the electronic health record. Logistic regressions were performed to estimate associations between race and ethnicity and the clinical outcomes. Results: The study population (N = 2931) was stratified into 1 of 3 subgroups: non-Hispanic White (n = 466), non-Hispanic Black (n = 1611), and Hispanic (n = 654). The average age of White, Black, and Hispanic patients was 69 ± 17.06, 64 ± 15.9, and 50 ± 15.53 years old, respectively ( P < .001). Compared to White patients, Black and Hispanic patients were at increased odds of needing mechanical ventilation due to COVID-19 pneumonia (odds ratio [OR] Black = 1.35, 95% confidence interval [CI] = 1.04 to 1.75, P < .05; OR Hispanic = 1.43, 95% CI = 1.06 to 1.93, P < .05). When compared to White patients, Hispanic patients were at decreased odds of death (OR = 0.45, 95% CI = 0.32 to 0.63, P < .001). However, when adjusting for age, there were no statistically significant differences in the odds of death between these groups (adjusted OR [aOR] Black = 1.05, 95% CI = 0.80 to 1.38, P = .71; aOR Hispanic = 1.10, 95% CI = 0.76 to 1.60, P = .62). Conclusion: Our analysis demonstrated that Hispanic patients were more likely require mechanical ventilation but had lower mortality when compared to White patients, with lower average age likely mediating this association. These findings emphasize the importance of outreach efforts to communities of color to increase prevention measures and vaccination uptake to reduce infection with COVID-19.